Immigration and Violence in Rural versus Urban Counties, 1990–2010. Issue 2 (3rd April 2017) - Klein, Brent R.; Allison, Kayla; Harris, Casey T.
ABSTRACT: Extending disorganization and immigrant revitalization perspectives beyond the contexts dominating prior research, this study examines whether and how immigration may be uniquely linked to crime in rural versus urban communities over the 1990–2010 period. Drawing on the Uniform Crime Reports offenses known database and the United States Census, we find that increases in immigration are negatively associated with violence. However, this relationship varies considerably across urban and rural locales. Our analysis reveals that immigration has no effect on crime in the most rural communities, but buffers against it in the most urban ones. Additional regional variation in these urban and rural differences is also revealed.